PROTECTIVE ROLE OF TOPSIN M 70 FUNGICIDE AND SILICON OXIDE AGAINST WHITE MOLD DISEASE ON TWO CULTIVARS OF EGGPLANT - Abdulkhaleq, Zahraa H.; Abdul-Karim, Eman K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was conducted at the Plant Protection Directorate / Technical Departments Complex in 2023 to identify the causal agent of white mold disease and evaluate the effectiveness of the fungicide Topsin M 70 and silicon oxide in controlling disease progression, infection rate, and severity. The results indicated that the Sclerotinia sclerotiorum (SS5) isolate exhibited the highest pathogenicity, with an infection rate of 100% and a severity of 82.5%. DNA electrophoresis analysis of the SS5 isolate revealed a single band with a molecular weight of 550 bp, showing 100% similarity to globally registered isolates in the NCBI gene bank. The nucleotide sequences were registered under accession number OR497817. The application of nano-silicon oxide (0.001 g/L), conventional silicon oxide (3 g/L), and the chemical fungicide Topsin M 70 (1 g/L) as foliar sprays on Solanum melongena cultivars Wasam and Barcelona exhibited protective effects. The chemical fungicide provided complete disease suppression, recording 0% infection rate and severity in both cultivars. Nano-silicon oxide resulted in an infection rate of 13.87% and severity of 5.44%, while conventional silicon oxide recorded 63.16% infection rate and 7.43% severity, compared to the control, which showed 50% infection rate and 25.69% severity. The area under the disease progression curve (AUDPC) was 130.95 and 143.21 in the control treatment, but it dropped to 0% with the application of the chemical fungicide.